PRAANGGAPAN DAN IMPLIKATUR DALAM Mr. PECUT PADA JAWA POS - Retnosari, Ira Eko (LPPM Universitas PGRI Adi Buana Surabaya, 2014)
Discourse is a complete recording language of communication events. Communication can apply the spoken language and written language. Knowing discourse analysis is required. Analysis matters relate to discourse is imp licatures, presuppositions, inference, and references. According to Stalnsker (Kartom ihardjo in Pelba 6 , 1993:30), the presmption of sharing knowledge (common ground) between speaker and listener so it does not need to be expressed. Meanwhile, Grice (Kartomihardjo in Pelba 6, 1993:30) argues that implicatures is a speech that implies something different to the exact pronounced. This study applies a qualitative approach. The source of this research is Jawa Pos daily data while the data of this study are the sentences contained in Mr. Pecut's discussion. The results of this study are Mr. Pecut's on Jawa Pos daily containing presuppositions and implicatures. Sentences in Mr. Pecut's bold letters implied that presuppositions contained whereas sentences are in italics containing implicatures. In written language, prejudice is something that is used as the common ground between the writer and the reader. Mistakes made have the impact of presuppositions of speech. Meanwhile, the probability of implicatures are meant by the speaker with speech can never be known exactly. Implicature is easily understood by the speaker and the opponent if they know each other and have the same experienced topic